Understanding impacts of flow rate on performance of desalination flow batteries. (September 2021) - Wang, F.; Wu, W.; Lu, Z.; Yuan, B.; Zhao, Y.; Liu, T.L.
Abstract: It is critical to develop more efficient and cost-effective desalination technologies capable of fully seawater desalination capacity to meet the grand freshwater scarcity challenge. Desalination flow batteries are an emerging electrochemical device capable of integrated energy storage and desalination and represent a promising electrochemical technology for scalable and cost-effective desalination of seawater. Herein, we report the impacts of flow rate on the performance of a methyl viologen/sodium ferrocyanide (MV/Na4 [Fe(CN)6 ]) desalination flow battery (DSRFB). It was found that the increase of the flow rate can lower the battery resistance and improve energy efficiencies, power density, and desalination efficiency. Specifically, increasing the flow rate from 20 to 60 mL/min with an increment of 20 mL/min, the MV/Na4 [Fe(CN)6 ] DSRFB manifested an increase of energy efficiency from 56% to 64%, and an increase of power density from 14.72 to 15.33 mW/cm 2 . More importantly, the desalination percentage of the DSRFB was increased from 86.9% at 20 mL/min to 93.9% at 60 mL/min. Highlights: Flow rate impacts of a viologen/ferrocyanide desalination flow battery were studied. Flow rate can lower battery resistances to improve energy and desalination efficiencies. Desalination percentage of 93.9% was achieved for 0.56 M simulated seawater. Graphical abstract: Image 1